Pengembangan Bahan Ajar E-Modul Pada Pelajaran Ilmu Pengetahuan Sosial (IPS) Di Sekolah Menengah Pertama (SMP) - Eka Fitriani; Rambang Muharramsyah; Muhammad Iqbal (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study was motivated by the limited use of digital teaching materials in social studies learning at SMP Negeri 2 Sawang, while students need learning resources that are visual, contextual, and accessible. This research aimed to develop an interactive e-module entitled "Tantangan Pembangunan Indonesia" based on Canva and Heyzine, and to examine its validity, practicality, and effectiveness in improving students' learning outcomes. The study employed Research and Development (R&D) using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The subjects involved 32 ninth-grade students, one social studies teacher, and three expert validators covering material, media, and language aspects. Data were collected through interviews, observation, expert validation sheets, teacher and student response questionnaires, and pretest-posttest learning outcome tests. The findings show that the e-module was categorized as very feasible based on material validation (88.5%), media validation (95%), and language validation (92%). The practicality test also indicated a very practical category, with student responses reaching 89% and teacher responses reaching 95%. The effectiveness test showed a significant increase in learning outcomes, as indicated by the paired sample t-test value of Sig. 0.000 < 0.05 and an average N-Gain score of 0.75 in the high category. These results indicate that the e-module is feasible, practical, and effective as an interactive teaching material for social studies learning. The product contributes to strengthening contextual digital learning, student independence, and teacher innovation in developing technology-based learning media.